2006
DOI: 10.1002/ajmg.b.30267
|View full text |Cite|
|
Sign up to set email alerts
|

Characteristics of the broader phenotype in autism: A study of siblings using the children's communication checklist‐2

Abstract: Non-autistic relatives of people with autistic disorder have an increased risk of social and communicative difficulties: this is known as the "broad phenotype." Better methods for characterizing the broad phenotype are needed to facilitate identification of risk genes for autism. 29 siblings of 20 children with autistic disorder, 13 siblings of 9 children with PDDNOS, and 46 typically developing control children from 26 families were assessed by parental report using the Children's Communication Checklist-2 (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
86
0
10

Year Published

2006
2006
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(109 citation statements)
references
References 16 publications
12
86
0
10
Order By: Relevance
“…99 Language abilities, however, were not impaired in siblings of children with autism 100 arguing against language abilities as a marker for the BAP. Two other studies, however, did find a reduced variance within autistic sib-ships regarding the onset of phrase speech, 101 and an influence of language abilities on the correlation of ICD-10 autism symptoms and the presence of the BAP in relatives, 102 arguing for a role of language abilities in the genetics of AD.…”
Section: Family Studiesmentioning
confidence: 97%
“…99 Language abilities, however, were not impaired in siblings of children with autism 100 arguing against language abilities as a marker for the BAP. Two other studies, however, did find a reduced variance within autistic sib-ships regarding the onset of phrase speech, 101 and an influence of language abilities on the correlation of ICD-10 autism symptoms and the presence of the BAP in relatives, 102 arguing for a role of language abilities in the genetics of AD.…”
Section: Family Studiesmentioning
confidence: 97%
“…60 Finally, diagnosis of an ASD may be made in an older family member with milder symptoms that were previously unrecognized until after the diagnosis of a younger child. 61 Regardless of the study, the year conducted, or the reported rate of prevalence, more boys than girls are consistently found to be affected with ASDs, with maleto-female ratios ranging from 2:1 to 6.5:1. 24,28,29,34,62 The male-to-female ratio is even higher for high-functioning autism and AS, ranging from 6:1 to as high as 15:1.…”
Section: Table 2 Diagnostic Criteria For 29980: Asperger's Disorder mentioning
confidence: 99%
“…Recently, the search for endophenotypes has led to the definition of the "Broader Autism Phenotype," in which certain impairments in joint attention, language, and social interaction have been isolated in "typical" family members of children with autism (Bailey and Parr 2003;Bishop et al 2006;Bolte et al 2007;Bolte and Poustka 2006;Dawson et al 2002aDawson et al , b, 2007Ruser et al 2007;Scheeren and Stauder 2007;Stone et al 2007;Sullivan et al 2007;Sung et al 2005). In one representative study, Dawson's group performed a study of face processing using ERPs in parents of children with autism and found, behaviorally and electrophysiologically, that parents of children with autism did not show the expected preference for faces over objects.…”
Section: The Futurementioning
confidence: 99%